Oxycelulosa--celulosový derivát s potenciálem ucinné i pomocné látky - Gajdziok, J; Bajerová, M; Chalupová, Z; Masteiková, R (Ceska a Slovenska farmacie, 2007)
The review article is focused on one of the wide range of pharmaceutically and medicinally employed cellulose derivates--oxycellulose. This substance, prepared by oxidation of cellulose, in contrast to cellulose esters and ethers, has not been not employed in practice in a wide extent yet. However, recent studies reveal its potential use in modern therapeutical systems, whether as a release-modifying excipient, a drug carrier, or also an active substance with ability of hemostasis, prevention of tissue adhesion after surgical operations, and a substance with antimicrobial and immunomodulating activity, whose unique property of biodegradability, promoted by hypoallergenicity and non-irritability, has not been observed in any of the hitherto used cellulose derivates. The article presents a comprehensive overview about the history of this derivate, from its physico-chemical properties through the description of the ability of biodegradability to its already realized and planned utilization.
Keywords: Hypromellose Derivatives; methylcelulosa; Chemistry, Pharmaceutical; farmaceutická chemie; Pharmaceutic Aids; deriváty hypromelózy; farmaceutické pomocné látky; Methylcellulose